The characteristics of patients with bilateral absent evoked potentials after post-anoxic brain damage: A multicentric cohort study. (April 2020) - Nobile, Leda; Pognuz, Erik Roman; Rossetti, Andrea O.; Franchi, Federico; Verginella, Francesca; Mavroudakis, Nicolas; Creteur, Jacques; Berlot, Giorgio; Oddo, Mauro; Taccone, Fabio Silvio
Abstract: Objectives: Patients with bilateral absence of cortical response (N20ABS ) to somatosensory evoked potentials (SSEPs) have poor neurological outcome after cardiac arrest (CA). However, SSEPs are not available in all centers. The aim of this study was to identify predictors of N20ABS . Methods: Retrospective analysis of institutional databases (2008–2015) in three ICUs including all adult admitted comatose patients undergoing SSEPs between 48 and 72 h after CA. We collected clinical (i.e. absence of pupillary reflexes, PLR, myoclonus and absent or posturing motor response and myoclonus on day 2–3), electroencephalographic (EEG; i.e. unreactive to painful stimuli; presence of a highly malignant patterns, such as burst-suppression or flat tracings) findings during the first 48 h, and the highest NSE levels on the first 3 days after CA. Unfavorable neurological outcome (UO) was assessed at 3 months using the Cerebral Performance Categories of 3–5. Results: We studied 532 patients with SSEPs, including 143 (27%) without N20ABS ; UO was observed in 334 (63%) patients. Median time to SSEPs was 72 [48–72] h after CA. No patient with absent PLR and myoclonus during the ICU stay had N20 present; similar results were observed with the combination of absent PLR, myoclonus and any EEG pattern (i.e. unreactive or highly malignant). Similar results were observed in the subgroup of patients where NSE was available (n = 303). In a multivariate logistic regression, non-cardiac etiology of arrest, unreactive EEG to painful stimuli, absence of pupillary reflexes and posturing motor response, were independent predictors of N20ABS . When available, the highest NSE was also an independent predictor of N20ABS . Conclusions: Clinical and EEG findings predicting patients with N20ABS, confirm that N20ABS reflects a severe and permanent cerebral damage after CA.